Life, Fish and Mangroves: Resource Governance in Coastal Cambodia - Marschke, Melissa (Les Presses de l'Université d'Ottawa / University of Ottawa Press, 2012)
In Life, Fish and Mangroves, Melissa Marschke explores the potential of resource governance, offering a case study of resource-dependent village life. Following six households and one village-based institution in coastal Cambodia over a twelve-year period, Marschke reveals the opportunities and constraints facing villagers and illustrates why local resource management practices remain delicate, even with a sustained effort. She highlights how government and business interests in community-based management and resource exploitation combine to produce a complex, highly uncertain dynamic. With this instructive study, she demonstrates that in spite of a significant effort, spanning many years and engaging many players, resource governance remains fragile and coastal livelihoods in Cambodia remain precarious.
Prologue Introduction Chapter 1: Desiring local resource governance Chapter 2: Governing a coveted resource Chapter 3: Life in a resource-dependent village, 1998 to 2010 Chapter 4: Villagers pursuing local resource governance, 1998 to 2010 Chapter 5: Resource governance across administrative units Chapter 6: Probing the failures Conclusion: Resource governance at the margins References Notes